Sleep habits and sleep characteristics at 1 year-old in the ELFE birth cohort study. (13th November 2019) - Messayke, S; Franco, P; Forhan, A; Dufourg, M N; Charles, M A; Plancoulaine, S
Abstract: : Infant sleep plays a critical role in his/her normal development. Sleep problems, including sleep onset difficulties (SOD) and night waking (NW), ranges from 20% to 30% in infants and young children and are partially persistent over time up to adulthood. French young children seem to have longer sleep durations and less sleep troubles than their counterparts worldwide. We here aimed at describing infants sleep characteristics (duration/24h (TST), NW, and SOD) and associated sleep habits in infants aged 1 year old from the French nationwide birth cohort ELFE. This study included 11, 571 infants with information on both sleep characteristics and sleep habits (parental presence when falling asleep, eating to fall asleep, sucking pacifier or finger to sleep and the location where the infant falls asleep and ends his/her sleep). Associations were studied using multinomial logistic regressions adjusted for familial and infant characteristics. Mean TST was 13hrs36 including 2hrs54 of naps, 20% of the infants had TST ≤12hrs/24h. About 46% did not present SOD or NW, while 16% had frequent SOD and 22% had NW > 1 night over 2. Parental presence, feeding to fall asleep and infants sleep location were more frequent in infants having short sleep duration (≤12h/24h), NW and SOD. Non-nutritive sucking was associated with NW, SOD and TST>14h/24h. This work provides new information regarding infant sleep location and non-nutritive sucking that should be accounted for when considering sleep behaviors. In addition, most of identified sleep habits associated with poor sleep characteristics are accessible to prevention. Key messages: French infants present better sleep characteristics than their counterparts. Most sleep habits associated with poor sleep are accessible to prevention.